Śrīkrṣṇajanmāṣṭamīnirṇayaḥ : jayantīvratatithyādisametaḥ - Ratnākaradīkṣita, 18th cent ("Śrīveṅkaṭeśvara" (Sṭīm) Yantrālaye, 1901)
Manual for Hindu rituals and religious observance; portion deals with fasting on birthday of Krishna (Hindu deity)